Durability properties of structural concretes containing secondary cementitious materials. Issue 1 (3rd September 2018) - Li, Kefei; Qin, Minfeng; Gui, Qiang
Abstract : This study investigated the durability properties of structural concretes incorporating secondary cementitious materials of fly ash and ground granulated blast-furnace slag (GGBS). The compressive strength and porosity were taken as basic properties, and the transport properties measured included electrical conductivity, chloride diffusivity, capillary absorption and gas permeability. Correlation analysis was performed on the basic and transport properties, and the pore structure of structural concretes was characterized into different patterns in terms of the connectivity and the tortuosity. The results show that ( a ) the concrete pores are refined by mineral admixtures and Archie's law can describe the pore connectivity and tortuosity for saturated specimens; ( b ) all the transport properties correlate well with water-to-binder ( w / b ) ratios and the concretes with GGBS show a pronounced effect of oven-drying and self-desiccation on pore structure; and ( c ) chloride diffusivity and surface sorptivity correlate better with compressive strength, while chloride diffusivity, sorptivity and gas permeability should be treated as independent properties.